A Sizable Aortic Root Paravalvular Mycotic Pseudoaneurysm - Ahmad Saeed Azhar; Noran M. Abu-Ouf (Case Reports in Cardiology)
Mycotic aneurysm is an established condition first identified in 1885 by Sir William Osler. It is linked to malignant endocarditis. With prevalence of 0.7–2.6% of all cases of aortic aneurysms, it is associated with a significant rate of mortality and morbidity. Physicians should be highly cautious, as diagnosis and effective treatment for this condition are difficult. The following is a case report of a 13-year-old pediatric patient diagnosed with mycotic aneurysm. Before an adequate treatment plan could be developed and implemented, patient’s status worsened swiftly and was ultimately terminal. This case is the sole instance of this condition evidenced in the last ten years in Saudi Arabia.